An Efficient Hybrid DSMC/MD Algorithm for Accurate Modeling of Micro Gas Flows (Communications in Computational Physics, 2014)
Aiming at simulating micro gas flows with accurate boundary conditions,an efficient hybrid algorithm is developed by combining the molecular dynamics (MD)method with the direct simulation Monte Carlo (DSMC) method. The efficiency comesfrom the fact that the MD method is applied only within the gas-wall interaction layer,characterized by the cut-off distance of the gas-solid interaction potential, to resolve accurately the gas-wall interaction process, while the DSMC method is employed in theremaining portion of the flow field to efficiently simulate rarefied gas transport outside the gas-wall interaction layer. A unique feature about the present scheme is thatthe coupling between the two methods is realized by matching the molecular velocitydistribution function at the DSMC/MD interface, hence there is no need for one-to-one mapping between a MD gas molecule and a DSMC simulation particle. Furtherimprovement in efficiency is achieved by taking advantage of gas rarefaction insidethe gas-wall interaction layer and by employing the "smart-wall model" proposed byBarisik et al. The developed hybrid algorithm is validated on two classical benchmarks namely 1-D Fourier thermal problem and Couette shear flow problem. Boththe accuracy and efficiency of the hybrid algorithm are discussed. As an application,the hybrid algorithm is employed to simulate thermal transpiration coefficient in thefree-molecule regime for a system with atomically smooth surface. Result is utilized tovalidate the coefficients calculated from the pure DSMC simulation with Maxwell andCercignani-Lampis gas-wall interaction models.